Promising natural compounds against flavivirus proteases: Citrus flavonoids hesperetin and hesperidin - Eberle, Raphael J.; Olivier, Danilo S.; Amaral, Marcos S.; Willbold, Dieter; Arni, Raghuvir K. [UNESP]; Coronado, Monika A. (MDPI, 2021)
Ubiquitous in citrus plants, Hesperidin and Hesperetin flavanones possess several biological functions, including antiviral activity. Arbovirus infections pose an ever-increasing threat to global healthcare systems. Among the severe arboviral infections currently known are those caused by members of the Flavivirus genus, for example, Dengue Virus—DENV, Yellow Fever Virus— YFV, and West Nile Virus—WNV. In this study, we characterize the inhibitory effect of Hesperidin and Hesperetin against DENV2, YFV, and WNV NS2B/NS3 proteases. We report the noncompetitive inhibition of the NS2B/NS3pro by the two bioflavonoids with half maximal inhibitory concentration (IC50) values < 5 µM for HST and <70 µM for HSD. The determined dissociation constants (KD) of both flavonoids is significantly below the threshold value of 30 µM. Our findings demonstrate that a new generation of anti-flavivirus drugs could be developed based on selective optimization of both molecules.
Keywords: Flavivirus; Hesperetin; Hesperidin; Noncompetitive inhibitors; NS2B/NS3pro